Staphylococcus aureus: the host-organism relationship - Miller, R; Ruth Miller (2011)
Staphylococcus aureus is a worldwide leading cause of skin and soft tissue, bone and joint, and bloodstream infection. Despite this, S. aureus is also a harmless commensal in about one third of the population, although carriage is a risk factor for subsequent disease. S. aureus has evolved resistance to several antibiotics, including meticillin, resulting in meticillin-resistant S. aureus (MRSA), which in the UK largely consists of two epidemic lineages. In spite of much research, substantial aspects of the epidemiology and biology of S. aureus are still poorly understood. In investigating the S. aureus host-organism relationship, this thesis has three aims. To explore the interface between community and hospital-acquired S. aureus; to investigate the carriage dynamics of S. aureus in the community; and to use population genetic methods to study epidemic hospital associated S. aureus lineages. Case-control studies comparing hospital and community-acquired MRSA revealed that the majority of UK MRSA remains healthcare associated, with community-acquired MRSA reliably identified in only 0.2% of individuals. However, an additional 0.2% of individuals also carried "feral" MRSA with molecular characteristics identical to hospital-associated strains, but in hosts with no healthcare risk factors. To further investigate S. aureus carriage dynamics in the community, a carriage study was designed to collect detailed host factor information and correlate this with S. aureus carriage over time. In the study 32% of participants carried S. aureus of which the majority carried for over one year. Younger age was associated with transient carriage, including S. aureus acquisition in individuals who were initially negative. Finally, whole-genome sequencing of two epidemic S. aureus lineages indicated rapid clonal expansion of MRSA and clear geographic and temporal genetic structure. One particularly closely related cluster of strains may provide a genetic explanation for an MRSA outbreak in Brighton.